Chalmers on bills of exchange : a digest of the law of bills of exchange, promissory notes, cheques, and negotiable securities - Smout, David A. L; . Chalmers, M. D.; Great Britain; Great Britain (London : Stevens, 1964)
This 13th edition offers legal practitioners comprehensive guidance to the to the law and practice relating to bills of exchange, cheques and promissory notes.
Includes Index
Bibliography
ucj, 15/01/2019
Loans
Keywords: Negotiable instruments